Optimal geometric arrangement of unfinned and finned flat tube heat exchangers under laminar forced convection - Tahseen Ahmad, Tahseen (2014)
This thesis describes the three-dimensional numerical analysis and experimental study of the heat transfer and flow characteristics in the un-finned and finned flat tube heat exchangers for in-line and staggered configurations. Flat tubes are vital components of various technical applications including modern heat exchangers, thermal power plants, and automotive radiators. The objectives of this research are to develop a numerical code to predict the thermal–hydraulic characteristics of laminar forced convective flow, to identify optimal spacing tube-to-tube and fin-to-fin for the maximum overall heat transfer rate and minimum power pumping of the fan between the tube bundle and surrounding fluid at the fixed volume and to develop a new correlation for overall heat transfer rate and power pumping in general and optimum configurations. Conservation equations (mass, momentum, and energy) were solved to develop code utilizing Visual-FORTRAN based on finite volume technique to determine the temperature and velocity fields. Subsequently, the overall heat transfer rate and power pumping among the tubes, fins, and fluid flow were calculated. The algorithm of semi-implicit method for pressure-linked equations was utilized to link the pressure fields with velocity. Finally, the subsequent set of discretization equations was solved with line-by-line method of the tri-diagonal matrix algorithm and the Gauss–Seidel’s procedure. Twelve fixed tubes were used in the experimental setup for flat tube configurations were obtained with these uniformly fitted tubes with a fixed volume. The experimental setups with several arrays of tubes and fins were fabricated with the same volume. The results were reported of the external air flow in a range of Reynolds numbers based on the hydraulic diameter of 178 to 1,470. It can be observed from the obtained results that the geometric optimum for tube-to-tube spacing was (St/dT 1.6) in the in-line configuration and (St/dT 2.0) in the staggered configuration. Meanwhile, fin-to-fin spacing was f = 0.025, according to general dimensionless variables. Up to 1.48 and 1.11 times (in-line) as well as 2.3 and 1.4 times (staggered) of heat transfer gain were noted in the optimal configuration for the low and high Reynolds numbers. A newly developed correlation of heat transfer rate and power pumping was then proposed. Approximately 87.5 % of the database described the heat transfer correlation within ± 15 % for the in-line configuration. For the staggered arrangement, 82% of the deviations were within ± 15 %. Up to 97.2 % of the database can be correlated with the proposed power pumping correlation within ± 18 % for the in-line arrangement, and 86.2% of the deviations were within ±15 % for the staggered arrangement. In the in-line configuration, the mean errors of the heat transfer and power pumping correlations were 9.5 % and 12.2 %, respectively. In the staggered configuration, the mean deviation errors of heat transfer and power pumping correlations were found to be 9.5 % and 11.1%, respectively. The predictive correlations developed in this study for in-line and staggered configurations can predict the heat transfer rate and power pumping of both un-finned and finned flat tube heat exchangers, which can be applied to the design of future heat exchangers in the industry.